Representation of Women in Sexual Violence News on Kompas.com : Sara Mills' Perspective - Midle Line Krismonsari; Prihadi (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2024)
The aim of this research is to describe the subject-object position of women in the sexual violence news kompas.com using Sara Mills' perspective. The subjects of this research are journalists and the objects of this research are women. Women who experience sexual violence are positioned as victims without resistance. This research data was taken from kompas.com using Sara Mills' critical discourse analysis. The research results in news text 1 show that the woman or victim is in the object position. The victim experienced an act of rape by her stepfather. The second news story shows the victim in the position of the object. The victim was still in elementary school and was molested by an old man. Victims not only experience harassment but are also threatened to keep quiet and given money to cover up the perpetrator's behavior. The third news shows women in the position of objects and as victims.